Fabrication of heterogeneous chemical patterns on stretchable hydrogels using single-photon lithography. Issue 23 (30th May 2022) - Im, Haeseong; Heo, Eunseok; Song, Dae-Hyeon; Park, Jeongwon; Park, Hyeonbin; Kang, Kibum; Chang, Jae-Byum
Abstract : A curved, chemically heterogeneous hydrogel is achieved by patterning on the highly stretchable hydrogel. Abstract : Curved hydrogel surfaces bearing chemical patterns are highly desirable in various applications, including artificial blood vessels, wearable electronics, and soft robotics. However, previous studies on the fabrication of chemical patterns on hydrogels employed two-photon lithography, which is still not widely accessible to most laboratories. This work demonstrates a new patterning technique for fabricating curved hydrogels with chemical patterns on their surfaces without two-photon microscopy. In this work, we show that exposing hydrogels in fluorophore solutions to single photons via confocal microscopy enables the patterning of fluorophores on hydrogels. By applying this technique to highly stretchable hydrogels, we demonstrate three applications: (1) improving pattern resolution by fabricating patterns on stretched hydrogels and then returning the hydrogels to their initial, unstretched length; (2) modifying the local stretchability of hydrogels at a microscale resolution; and (3) fabricating perfusable microchannels with chemical patterns by winding chemically patterned hydrogels around a template, embedding the hydrogels in a second hydrogel, and then removing the template. The patterning method demonstrated in this work may facilitate a better mimicking of the physicochemical properties of organs in tissue engineering and may be used to make hydrogel robots with specific chemical functionalities.